HUBUNGAN TINGKAT PENGETAHUAN TERHADAP PENCEGAHAN DERMATITIS SEBOROIK PADA PELAJAR DI SMA NEGERI UNGGUL SIGLI - Surya Nola; Tasya Talitha Nadhillah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2021)
Seborrheic dermatitis is a chronic papulosquamosa skin disorder that occurs to anyone, caused by malassezia yeast and excess oil glands. Objective: aims to determine the knowledge of seborrheic dermatitis in students at Sigli Superior High School and prevention of seborrheic dermatitis in students in Sigli Superior High School. Methods: This study uses a cross-sectional approach, research variables consisting of seborrheic dermatitis (dependent) and knowledge and prevention in seborrheic dermatitis (independent). The sample in this study amounted to 43 people. Data collection using a questionnaire while analyzing data using frequency distribution analysis. Results: The results of the study note that there is no relationship between the Knowledge Level of Seborrheic Dermatitis Prevention in Sigul Superior High School students.Keywords: Knowledge, Prevention, Seborrheic dermatitis